Truth, Sense and Assertion*. (12th November 2015) - Anscombe, G.E.M.
Abstract: Protagoras and his pupil Euthalos argued against one another in paradoxical fashion regarding the fulfilment of a contract. Protagoras was a Sophist, the first European inventors of logical puzzles who also argued that there cannot be false thinking. A paradox, however, does not say anything, and there is no solution to the question as to who is right in the exchange between Protagoras and Euthalos. On the other hand there is a real question as to how it is that a false proposition makes sense, and the Sophists were right in as much as a false proposition, while it does say something does not, being believed, tell its believer anything. The exclusion of paradoxical propositions is not to be achieved, as Russell supposed, by applying some general principle; rather matters need arguing through in particular cases as they arise.